Lived Experiences of Adolescents with Internet Addiction - Suryani, Suryani; Sriati, Aat; Septiani, Nurul (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Internet addiction has been and will become a serious global problem in the future. Understanding the lived experiences of adolescents with internet addiction is crucial for providing appropriate nursing interventions.Purpose: This study aimed to explore the lived experiences of adolescents with internet addiction.Methods: This was a phenomenological study involving in-depth interviews with seven adolescents with internet addiction. Data were analyzed using Colaizzi’s approach of analysis.Results: Six themes were identified from this study: the feeling that playing with the internet is more important than the school; become “too lazy to move” and unable to manage time; physical health disorders due to internet addiction; the feeling that it is difficult to be away from the internet, and social interaction difficulties in the real world, which then leads to hostile attitude due to the lack of ability to control emotions.Conclusion: The lived experience of adolescents with internet addiction is complicated and impacted on all aspects of teenagers’ lives. These findings provide insights for nurses in preventing and overcoming internet addiction problems among teenagers.